2000
DOI: 10.1152/jappl.2000.89.2.636
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in visceral adipose tissue but not anthropometric markers of health-related variables

Abstract: This study sought to determine whether visceral adipose tissue (VAT) and/or its anthropometric surrogates could significantly predict health-related variables (HRV) in overweight Caucasian (CC) (n = 36) and African-American (AA) (n = 30) women. With the use of magnetic resonance imaging, findings showed significantly higher volume and area of VAT (P < 0.0001 for both) as well as higher triacylglycerol (P = 0.009) in CC compared with AA women. Furthermore, VAT volume, race, and VAT volume x race interaction cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 41 publications
(37 reference statements)
8
73
1
2
Order By: Relevance
“…As we previously reported, VAT volume was not associated with HOMA IR in AA women. 24 However, a report involving women who were more obese than those studied here and with comparable VAT between AA and CC showed no ethnic difference in the association between VAT and insulin resistance, 29 arguing in favor of the concept that a lower volume of VAT in AA might play a role in the ethnic differences we found. In order to clarify this point, we examined the relationship between VAT volume and PAI-1 in CC women in the lower one half of VAT values and found a strong positive correlation (r ¼ 0.66, P < 0.01), indicting that, at lower levels of VAT comparable to those in the AA group, VAT remained associated with PAI-1 in CC women.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As we previously reported, VAT volume was not associated with HOMA IR in AA women. 24 However, a report involving women who were more obese than those studied here and with comparable VAT between AA and CC showed no ethnic difference in the association between VAT and insulin resistance, 29 arguing in favor of the concept that a lower volume of VAT in AA might play a role in the ethnic differences we found. In order to clarify this point, we examined the relationship between VAT volume and PAI-1 in CC women in the lower one half of VAT values and found a strong positive correlation (r ¼ 0.66, P < 0.01), indicting that, at lower levels of VAT comparable to those in the AA group, VAT remained associated with PAI-1 in CC women.…”
Section: Discussioncontrasting
confidence: 49%
“…This group was a subset of women who participated in a study previously reported by us. 24 All subjects had a BMI greater than 25.0 kg=m 2 , were in good health, and were not taking any medications known to affect blood pressure, carbohydrate or lipid metabolism. Both parents and both grandparents had to be of the same racial descent for the subject to be considered CC or AA.…”
Section: Subjectsmentioning
confidence: 99%
“…For example, years of life lost due to obesity is significantly greater for Whites at nearly all ages than it is for Blacks [54], and this effect is particularly pronounced in women. This could be explained in part by the healthier (more subcutaneous) fat patterning that Black women have compared to White women at the same level of BMI [55,56]. On the other hand, obesity disparities in Black and White adults [6] and children [7] are more pronounced in females than in males, despite the fact that Black/White disparities in mortality and chronic disease occur across both men and women [1].…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Although differences in study methodology may account for the lack of consistency across studies, several studies suggest genetic or intrinsic physiological factors may underlie the differences in the prevalence of NAFLD in African Americans versus other racial groups. [31][32][33][34][35][36][37] We found that NAFLD patients who were of Asian race had a significantly lower BMI than all other racial groups. Although the World Health Organization currently defines overweight and obesity as a BMI of 25 kg/m 2 or more and 30 kg/m 2 or more, respectively, these definitions may vary by racial-ethnic group.…”
Section: Discussionmentioning
confidence: 99%